Bad tourists eaudiobook A novel. - Carver, Caro (Simon & Schuster Audio, 2024)
Three tight-knit friends embark on an extravagant divorce trip to the Maldives where they can unwind and celebrate a new chapter in midlife—until they realize the resort of their dreams is harboring a killer. Best friends Darcy, Camilla, and Kate escape for a post-divorce retreat in the Maldives, the perfect place to relax, reset, and embrace a fresh start in life. Darcy is learning how to be a free woman at forty-two. Camilla has found the perfect calling as a fitness and wellness influencer with a devoted following. And Kate is finally working on the book she was meant to write after years of telling other people's stories. Their dream getaway? The exclusive and isolated Sapphire Island Resort. With luxurious private villas, crystal-clear waters, and sun-drenched white sand beaches, relaxation is guaranteed. But this is no ordinary friendship, and they're not the only guests on the island with secrets. Who left the body on the beach—and who's next? A propulsive and deliciously dark tale about female friendship, loyalty, and lies, Bad Tourists is a white-hot thriller from the first page to its mind-blowing finish.